PENDAMPINGAN PENGELOLAAN DANA DESA - Usman; Joko Hariadi (Global Science Society, 2020)
The management of Nurussalam Subdistrict Village Fund management is responsible for the Head of the East Aceh Regency Level II Regional Head, based on East Aceh Regent Regulation Number: 2 of 2019 dated January 8, 2019 concerning Procedures and Distribution and Determination of the Details of Village Funds in 2019 and Qanun, in accordance with the Village Financial Management Regulations in the field of equalization of the Village Fund. A total of 31 Village Funds have been allocated by the Village Fund since 2015, the realization of Village Finance management according to planning, implementation, administration, reporting and accountability. Each village proposes a Village Fund to the East Aceh Regent Phase I (20%), destined for the provision of clean water / sanitation; providing nutritious food for toddlers, and posyandu for the health of pregnant women. Dedication Method; normative and empirical approaches and use primary and secondary data, and are processed descriptively qualitatively. The inhibiting factor in the Village Funds Financial management process is the delay in transferring money from the Center. Village Funds should have been received at the beginning of January 2019, in fact villages in Nurussalam Subdistrict received funds from the Center and District in early June 2019. This budget for reviewing village spending was deemed not on target, there was still a lack of supervision by the District Monitoring Team Level II Region of East Aceh Regency